Single‐Nucleus and Spatial Transcriptome Profiling Delineates the Multicellular Ecosystem in Hepatocellular Carcinoma After Hepatic Arterial Infusion Chemotherapy - YeXing Huang; ZeFeng Du; ZhiCheng Lai; DongSheng Wen; LiChang Huang; MinKe He; ZiChao Wu; HuiFang Li; HanYue OuYang; WenChao Wu; Anna Kan; Ming Shi (Advanced Science)
Abstract Hepatic arterial infusion chemotherapy (HAIC) has emerged as a promising treatment strategy for hepatocellular carcinoma (HCC), but a detailed understanding of the multicellular ecosystem after HAIC treatment is lacking. Here, we collected tumor samples from treatment‐naïve primary and post‐HAIC HCC, and integrated single‐nucleus RNA sequencing with spatial transcriptomics to characterize the tumor ecosystem in the post‐HAIC HCC. Increased fractions and enhanced cellular communication of CD4+ T, CD20+ B, and dendritic cell subtypes were identified in post‐HAIC tumors. Moreover, it is substantiated that HAIC promoted tertiary lymphoid structures (TLS) formation, and addressed the roles of TLSs as spatial niches of cellular communication. Specifically, intermediate exhausted CD8+ T cells expressing Granzyme‐K and PD‐1 (PD‐1+CD8+ Tex‐int) expanded following HAIC and exhibited a functionally antitumor phenotype. PD‐1+CD8+ Tex‐int accumulated in the TLS vicinity and disseminated throughout the tumor microenvironment, demonstrating potential as an effective biomarker for HAIC‐based treatment in HCC. This study provides valuable resources and biological insights in the cellular underpinnings of HAIC treatment.